The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/aoc.3647
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically recoverable copper nanorods and their catalytic activity in Ullmann cross‐coupling reaction

Abstract: A novel polydentate ligand supported on Fe 3 O 4 @SiO 2 was designed and demonstrated for the synthesis of Cu nanorods. The Fe 3 O 4 @SiO 2 /EP.EN.EG@Cu was characterized using X-ray diffraction, thermogravimetric analysis, transmission electron microscopy, energy-dispersive X-ray spectroscopy and vibrating sample magnetometry. The Fe 3 O 4 @SiO 2 /EP.EN.EG@Cu showed excellent catalytic efficiency for the cross-coupling reaction of nitrogen-containing heterocycles with aryl halides. The catalyst could be effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…From our previous study, we found that successfully synthesized Fe 3 O 4 @SiO 2 /EP.EN.EG.Cu can be used as a highly efficient robust in the reduction of nitro compounds and Ullmann cross‐coupling reaction under mild conditions. This results encouraged the authors to study catalytic efficiency in other reaction, herein we report a simple and efficient methodology for the synthesis of 1,4‐disubstituted‐1,2,3‐triazole.…”
Section: Resultsmentioning
confidence: 99%
“…From our previous study, we found that successfully synthesized Fe 3 O 4 @SiO 2 /EP.EN.EG.Cu can be used as a highly efficient robust in the reduction of nitro compounds and Ullmann cross‐coupling reaction under mild conditions. This results encouraged the authors to study catalytic efficiency in other reaction, herein we report a simple and efficient methodology for the synthesis of 1,4‐disubstituted‐1,2,3‐triazole.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of Fe 3 O 4 @SiO 2 /EP.EN.EG@Cu. Reprinted with permission from Rajabzadeh et al [ 149 ] Copyright 2017 John Wiley and Sons…”
Section: Copper Nanocatalystsmentioning
confidence: 99%
“…EN.EG@Cu. Reprinted with permission from Rajabzadeh et al [149] Copyright 2017 John Wiley and Sons S C H E M E 1 9 N-arylation of different nitrogen-containing heterocycles with aryl halides catalyzed by Fe 3 O 4 @SiO 2 /EP.EN.EG@Cu S C H E M E 2 0 N-arylation of imidazole with different aryl halides using Fe-CuO S C H E M E 2 1 N-arylation of different heterocycles with 4-bromobenzonitrile using Fe-CuO T A B L E 6 Fe 3 O 4 @SiO 2 -DAQ-Cu (II)-catalyzed N-arylation of N(H)-heterocycles and amines with various aryl halides F I G U R E 6 Preparation of the maghemite-Cu nanocatalyst. Reprinted with permission from Sharma et al [152] Copyright 2015 John Wiley and Sons F I G U R E 7 Preparation of Cu/ascorbic acid@MNPs.…”
Section: Maghemite-cu Nanocatalysts (Magnetically Separable Cu Nanoca...mentioning
confidence: 99%
“…[ 1–7 ] Industry favors the application of heterogeneous catalysts over homogeneous processes in view of the ease of handling and simple work‐up and separations. [ 8–15 ] Because of the importance of environmental and economic issues, global scientific and industrial discoveries in the field of catalysts should use the principles of “Green Chemistry”. [ 16–23 ] Recovery and reusability which can be regarded as the two valuable keys attached to the catalytic reactions for the definition of sustainability indicate that a catalytic process follows the “Green Chemistry” principles.…”
Section: Introductionmentioning
confidence: 99%